Improvement of Rice Straw for Ruminant Feed Through Unconventional Alkali Treatment and Supplementation of Various Protein Sources - Suwandyastuti, SNO; Bata, M (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
Various chemical treatments were conducted to increase the utilization of rice straw as feed for ruminant animals. Various sources of protein, minerals and energy should be added to improve the nutritive value of feeds. Two experiments were conducted in this study. The objective of the first experiments was to study the effect of chemical treatment on the ruminal fermentation products in cattle. Unconventional alkali treatment made from filtrate of a 10% rice hulls ash solution enriched with urea and minerals (treatment 1) increased volatile fatty acid (VFA) production, ammonia nitrogen (NH3-N) and rumen microbial protein synthesis (MPS). The maximum values of NH3-N production and rumen microbial protein synthesis were reached at 4 hours after incubation, while VFA was reached at 6 hours. The second experiment was conducted to study the increase of nutritive value of rice straw previously treated in experiment 1 through supplementation with various protein sources. Protein sources from the residues of vegetative oil production such as coconut, peanut and soybean showed higher responses compared to soy-sauce making residue and tofu making residue. The protein effluent production was highest (2.19 g/d) at a VFA/NH3-N ration of 37.74 (r = 0.912). It can be recommended that protein sources from agro-industrial wastes can be used to increase the nutritive value and utilization of rice straw as ruminant feed. (Animal Production 12(2): 82-85 (2010)Key Words: rice straw, rumen, fermentation